Bagaimana Harga Input dan Kuantitas Output Berpengaruh Terhadap ROE Bank (Studi kasus pada PT. Bank X) - Iman Sidik Nusannas (Eqien - Jurnal Ekonomi dan Bisnis, 2018)
Researchs related to bank efficiency, had been written down for many years ago and resulted many papers. Berger and Humprey(1997) wrote 130 papers for this topic by taking sample in many countries. The results are more banks in developing countries are efficient, and among of them small banks have a good efficiency score compared to large scale banks. Darrat et.al (2002) found the level of efficiency of banks in Kuwait has a good correlation with Berger and Humpreys research. Altunbas, Yener et.al (2001) made a study for measuring bank efficiency in German by using variables input price and output quantity,This paper use those variables to see the impact of input price and quantity output to the bank profitability proxied by ROE (Case study in PT. Bank X). The result are the higher output quantity variables the higher ROE of the bank. And the lower input price variables the higher ROE of the bank.